KOMPOSISI HASIL TANGKAPAN IKAN DAN TINGKAT KERAMAHAN LINGKUNGAN ALAT TANGKAP JARING INSANG DI KUALLO SOKKAM, SUMATERA UTARA - Irwan Limbong; Fitri Ariani; Teguh Heriyanto (Universitas Muhammadiyah Gresik, 2023)
The development of fishing technology emphasized environmentally friendly technology in hopes of utilizing a sustainable fishery resource and knowing the type and composition of fish catches. The purpose of this research is to know the composition of fish catches and the level of environmental friendliness of the net capture equipment based on the FAO (1995). The method used in this study was a survey method with 2 objects of the Fish capture equipment unit. The composition of fish catches by type consists of 8 species. The species dominated by the type of fish is the female bloating (Rastrellinger brachysoma) amounting to 34%. The value of environmental friendliness of the gill net capture is 26. Based on the number of values categorized as a friendly capture tool that is a friendly environment.